2013
DOI: 10.1007/s10815-013-9938-8
|View full text |Cite
|
Sign up to set email alerts
|

Caspase signalling pathways in human spermatogenesis

Abstract: Purpose Little is known about the apoptotic mechanisms involved in abnormal spermatogenesis. In order to describe the significance of apoptosis in azoospermia, testicular tissue from abnormal spermatogenesis was analysed. Methods Testicular treatment biopsies were obtained from 27 men. Five presented oligozoospermia, 9 obstructive azoospermia (4 congenital bilateral absence of the vas deferens; 5 secondary azoospermia) and 13 nonobstructive azoospermia (5 hypospermatogenis; 3 maturation arrest; 5 Sertoli-cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 32 publications
(47 reference statements)
3
33
0
2
Order By: Relevance
“…Although the capacity of mature sperm to carry out apoptosis has been questioned due to the paucity of cytoplasm, it is well known that human sperm can possess apoptotic markers and that this may influence sperm function and perhaps be involved in the removal of DNA-damaged sperm in the female reproductive tract , or, alternatively, result from leftover apoptotic phenomena in the testis, possibly related to cases of male infertility (Almeida et al 2013). It is worth mentioning that some studies note increases in sperm DNA damage as evidence for apoptosis, but, while DNA damage is certainly one of the main consequences of apoptosis, apoptosis may not be the only possible mechanism involved , Aitken & De Iuliis 2010, Sakkas & Alvarez 2010, and the notion of DNA damage directly linked to a canonical apoptosis cascade in sperm has been questioned .…”
Section: Apoptosismentioning
confidence: 99%
“…Although the capacity of mature sperm to carry out apoptosis has been questioned due to the paucity of cytoplasm, it is well known that human sperm can possess apoptotic markers and that this may influence sperm function and perhaps be involved in the removal of DNA-damaged sperm in the female reproductive tract , or, alternatively, result from leftover apoptotic phenomena in the testis, possibly related to cases of male infertility (Almeida et al 2013). It is worth mentioning that some studies note increases in sperm DNA damage as evidence for apoptosis, but, while DNA damage is certainly one of the main consequences of apoptosis, apoptosis may not be the only possible mechanism involved , Aitken & De Iuliis 2010, Sakkas & Alvarez 2010, and the notion of DNA damage directly linked to a canonical apoptosis cascade in sperm has been questioned .…”
Section: Apoptosismentioning
confidence: 99%
“…Accordingly, altered expression patterns of a panoply of apoptosis-related genes have been described in human testes with defective spermatogenesis. The association of death receptors and the extrinsic pathway of apoptosis with male infertility have been suggested by several studies, which showed enhanced expression of FasL in cases of maturation arrest and Sertoli cell-only syndrome, the later characterised by the absence of germ cell in the seminiferous epithelium ( Refs 5,34,35,36,37,38). Cavalcanti et al found an increased expression of tumour necrosis factor alpha (TNF-α) family member 10 (also known as TNF-α-related apoptosis inducing ligand, TRAIL) in the testes of subfertile men comparatively with potentially fertile (Ref.…”
Section: Clinical Findings Of Deregulated Apoptosis In the Testis Of mentioning
confidence: 99%
“…Recent studies report that caspase signal pathways are relative to the apoptosis of germ cells 1617. However, whether the function of caspase 7 is involved in spermatogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%